Evolution of radiopulses radiated by Hertz's dipole in vacuum - Naydenko, V.; Piltyay, S. (2008 12th International Conference on Mathematical Methods in Electromagnetic Theory, 2008)
Properties of the fields and power descriptions are considered. It is shown that the form of radiopulses in a distant area is determined by a derivative from the form of impulse of current, given on Hertzpsilas dipole. Power descriptions of the electromagnetic field are proportional to the square of derivative from the form of impulse of current, given on Hertzpsilas dipole.